Simultaneity of green energy and hydrogen production: Analysing the dispatch of a grid-connected electrolyser - David Schlund; Philipp Theile (Institute of Energy Economics at the University of Cologne (EWI), 2021)
Hydrogen is viewed as a promising supplement in future energy systems with high penetration rates of renewable energy (RE) generation. As conversion technology between the two secondary energy carriers, hydrogen and electricity, particularly grid-connected electrolysers, have a role to play. During the market ramp-up, grid-connected electrolysers could cause unwanted side-effects through inducing additional CO2 emissions from the power sector. Since the reduction of CO2 remains the overall goal, a simultaneity obligation between RE generation and hydrogen production for the dispatch are being discussed to limit associated emissions from an electrolyser's energy consumption. The paper presents a model framework including a mixed-integer linear program and a Markov chain Monte Carlo simulation for stochastic electricity market prices to assess a grid-connected electrolyser's dispatch. Within a case study representing the current state of the German electricity market, the effect of simultaneity on the electrolyser's dispatch is assessed. The results show that the simultaneity reduces the CO2 emission intensity of hydrogen while constraining the profits from cost-optimal dispatch. The simultaneity represents implicit storage of the RE generation's green characteristic, which allows the electrolyser to shift RE production to low price periods. Depending on the simultaneity interval, this affects both the average contribution margin and the risk of the electrolyser dispatch. Regulations aiming at the interface between hydrogen and electricity must consider the trade-off between the economic viability of electrolysers, fullload hours, and the associated emissions of electricity-based hydrogen.
Keywords: C61; L51; M20; Q41; Q42; Q48; 330; hydrogen; power-to-gas; renewable energy support; optimisation